Investigation of Effect of Acetamiprid and d-Tubocurarine on Frog Nerve Tissue (I: Oxidative Potential) - Çamlıca, Yusuf; Salih Cüfer Bediz; Yalın, Serap (Journal of Research in Pharmacy, 2017)
The aim of this study is to investigate the oxidative stress effect of acetamiprid and d-tubocurarine on the sciatic nerve of Rana ridibunda by using biochemical methods. For this purpose, 40 frog sciatic nerve preparations were used in the experiments established. Frog sciatic nerves were isolated after making them spinal. Four different concentrations of acetamiprid solution (1×10-3, 1×10-4, 1×10-5 and 1×10-6 M) were applied on nerves for 120 minutes. In addition, the sciatic nerve tissues were maintained for 120 minutes in the mixture of 1x10-3 M acetamiprid and 1x10-2 M d-tubocurarine, the mixture of 1x10- 5 M acetamiprid and 1x10-4 M d-tubocurarine, the mixture of 1x10-6 M acetamiprid and 1x10-5 M d-tubocurarine. Nerve tissues in the control group were maintained in Ringer's solution for 120 minutes. The agonist and antagonist effects were studied in the experimental group and equal number of subjects (N = 5). Activity of catalase (CAT) and acetylcholinesterase (AChE) as well as malondialdehyde (MDA) levels were measured to evaluate oxidative stress in frogs. The results of the biomarker analysis revealed that the application of 1x10-3 M acetamiprid on sciatic nerve significantly reduced the CAT and AChE activity compared to that of control group (P<0.05). In contrast, it was determined that, the same concentration of the insecticide significantly increased the level of MDA on nerve tissue compared to that of control group (P<0.05). The significant reduction of CAT and AChE and significant increase of MDA in the sciatic nerve due to acetamiprid indicate that this insecticide, depending upon the oxidative stress, causes damage on peripheral nerves in high concentrations.